Pengaruh Budaya Organisasi dan Disiplin Kerja Terhadap Kepemimpinan pada PT Matoga Cipta Indonesia Kabupaten Deli Serdang - Mutiah Dwi Arisa; Kiki Farida Ferine; Teguh Wahyono (Cattleya Darmaya Fortuna, 2026)
This study aims to analyze the influence of organizational culture and work discipline on leadership at PT Matoga Cipta Indonesia. The research employed a quantitative approach with a population and sample consisting of 40 employees. Data analysis was conducted using validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination. The results show that organizational culture has a positive and significant effect on leadership, as indicated by a t-value of 4.086, which is greater than the t-table value of 2.021, and a signifi cance value of 0.000 < 0.05. Work discipline also has a positive and significant effect on leadership, with a t-value of 2.281, exceeding the t-table value of 2.021, and a significance value of 0.028 < 0.05. Simultaneously, both variables significantly influence leadership, as shown by an F-value of 15.506, which is higher than the F-table value of 3.25, and a significance value of 0.000 < 0.05. This study concludes that effective leadership is influenced by strong organizational culture and good work discipline. Therefore, the company should maintain a positive family-oriented culture while enhancing professionalism and work discipline to maximize leadership effectiveness.